A qualitative study of the experiences and perceptions of patients with functional motor disorder. Issue 14 (2nd July 2020) - Nielsen, Glenn; Buszewicz, Marta; Edwards, Mark J.; Stevenson, Fiona
Abstract: Background: Patients with functional motor disorder are perceived as difficult by health care professionals, but we know very little about the patients' perspective. Understanding the experiences and perceptions of patients could help to improve clinical services and patient outcomes. Purpose: To explore the experiences and perspectives of patients with functional motor disorder using qualitative research methods. Methods: This qualitative study was embedded within a feasibility study of specialist physiotherapy. Eleven patients with functional motor disorder participated in semi-structured qualitative interviews prior to receiving treatment. The interview transcripts were subjected to an inductive thematic analysis. Results: The data were arranged into six themes: (1) the burden of living with functional motor disorder; (2) nobody knew what was wrong; (3) dissatisfaction with psychological explanations; (4) patients feel abandoned; (5) iatrogenic harm; and (6) powerlessness. Discussion and Conclusion: The study participants experienced substantial physical and emotional burdens associated with functional motor disorder. They were generally dissatisfied with psychological explanations for their symptoms and commonly felt misunderstood and abandoned by health care professionals, which appeared to leave them vulnerable to iatrogenic harm. A lack of understanding of functional motor disorder left participants feeling unable to help themselves. This research highlights a number of inadequacies within current clinical services for patients with functional motor disorder. Implications for rehabilitation: Careful communication is required to help patients understand and accept the diagnosis of functional motor disorder. It is important to listen to the patient's narrative in order to help them make sense of their illness experience. A nuanced biopsychosocial explanatory model is needed to help patients understand how psychological factors can be relevant to physical symptoms and symptoms that are often perceived to be precipitated by a physical event. A lack of understanding and acceptance of the diagnosis may leave patients vulnerable to iatrogenic harm and powerless to help themselves.